The Evaluatıon Of The Relatıon Among Overbıte, Overjet And Angle Clasıfıcatıon - Meliha Rübendüz (Galenos Yayinevi, 2002)
In this study, it is aimed to examine if there is a relationship between the amount of overjet, overbite and the Angle classification in cases having orthodontic treatment indication. Six hundred and forty five individuals of any age, was included in the study. Overbite and overjet amounts and the Angle clasification were taken into consideration during the classification of the individuals but subdivisions of the Angle classification were not evaluated. The relations among the groups were evaluated using ''Chi-square" test. It was found that the amount of overbite and overjet were related with each other statistically. A close relationship was found also between the Angle classification and amounts of overjet and overbite.